The Absence of Durable Solutions, The Presence of Local Solutions in Protracted Refugee Situations. The Case Study of Uganda’s Approach to Hosting Refugees - Opono, Samuel; Ahimbisibwe, Frank; Twinamasiko, Specioza (Journal of Central and Eastern European African Studies, 2025)
The numbers of refugees have been increasing annually, engendering protracted refugee situations in the developing countries hosting refugees, yet with very minimal implementation of durable solutions. This intrigues the question of whether the approach of local solutions that empower protracted refugees to become resilient and self-reliant, can become a viable option to durable solutions especially in poor African countries such as Uganda? We use secondary literature and primary data collected from South Sudanese refugees in Uganda to answer this question. We argue that in the absence of granting or minimally granting refugees any of the three conventional durable solutions of repatriation, local integration and resettlement; the approach of local solutions can become an important but temporary (although long term) alternative for refugees to live relatively comfortable lives. However, this approach has to be holistically embraced and supported by various stakeholders, including the national government, local governments, international community, donors, and various nongovernmental organizations, to overcome the accompanying challenges and for the approach to succeed in empowering refugees to become resilient and self-reliant for a long time in their first asylum country and live a life outside camps or designated settlements, as they wait for any of the conventional durable solutions.